Servo control using pulse to pulse width modulation converter - Kartini, Mohamad Safiee (Universiti Malaysia Sarawak (UNIMAS), 2001)
Servos are used enormously in today's daily life. Examples of their applications are such as in CD player, vehicle's steering control, motors and many more. The function of the servo systems is to maintain the accurate flow of data. The servo operates based on the pulse width fed to it. This project is a study on a circuit that functioning as a converter for converting pulses to pulse width modulation (PWM) signal. The circuit is an interface between servo pulses and an H-Bridge that operate a motor. This study covered the stage by stage operation from beginning to the final stage on how the circuit works.